Adding Multiple Enzymes to Diets Containing Wheat Distillers Dried Grains with Solubles Improves Broiler Performance by Reducing Viscosity - Gouran, B.; Khorshidi, K. J.; Gharahveysi, S. (Tropical Animal Science Journal, 2025)
This study aimed to investigate the effects of adding the multienzyme Apsazyme (glucanase, xylanase, galactosidase, mannanase) to diets containing different levels of wheat distiller’s dried grains with solubles (WDDGS) on performance, ileal bacteria, intestinal viscosity, pH, and blood variables of broiler chickens. For this purpose, 300 one-day-old male and female broilers of the Ross 308 strain were used. The experimental diets included three levels of WDDGS (0%, 10%, and 20%) with and without multienzyme (125 g/ton). Data analysis was done using SAS statistical software as a factorial design. The use of 20% WDDGS reduced feed intake (FI) in the finisher period and total period compared to the control treatment (p<0.05). The use of 20% WDDGS level reduced body weight gain (BWG) compared to 10% WDDGS treatment (p<0.05). The feed conversion ratio (FCR) was significantly reduced in birds fed with 125 g/ton of multienzyme diet (p<0.05). The number of aerobes bacteria and coliform was higher in broiler chickens fed with 10% and 20% WDDGS diet compared to the control treatment (p<0.05). Also, the use of multienzyme increased the number of lactic acid bacteria in the ileum. Multienzyme supplementation significantly reduced the increase in intestinal viscosity and pH caused by the 20% WDDGS level (p<0.05). Using 20% WDDGS in the diet increased the serum albumin concentration compared to 10% and 0% WDDGS (p<0.05). Finally, it can be concluded that the use of multienzymes compensates for the negative effects of diets containing 20% ​​WDDGS on performance by reducing intestinal viscosity and modulating the gut microbial population. Therefore, it is recommended to add a multienzyme to the diet when using a 20% WDDGS level.